DEVELOPMENT OF A FOUR-TIER DIAGNOSTIC TEST TO DETECT MIDDLE SCHOOL STUDENTS' MISCONCEPTIONS IN ALGEBRAIC THINKING - Aristiawan, Aristiawan; Wilujeng, Hestu; Erwanto, Moh Rizky Yoga; Murtafiah, Wasilatul (FKIP Universitas Muhammadiyah Tangerang, 2025)
Misconceptions in algebra are a common issue encountered in mathematics learning. To address this problem, teachers and educators need tools that can accurately detect students' misconceptions. This study aims to develop a four-tier diagnostic test instrument to detect junior high school students' misconceptions in algebraic thinking. The type of research used is development research, adopting the Oriondo Dallo Antonio development model, which includes three stages: (1) test planning, (2) test trials, and (3) test trial result analysis. The trials were conducted in June 2024 with 118 seventh-grade students from junior high schools in Ponorogo. The data analysis used in this research includes several analyses, such as validity analysis using the product-moment correlation, reliability analysis using Cronbach's alpha, and item difficulty analysis using the Item Mean Difficulty (D) method under the classical test theory approach. The results showed that the four-tier diagnostic test instrument for diagnosing junior high school students' misconceptions in algebraic thinking consists of 17 valid items divided into four algebraic ability indicators: analytical thinking, problem-solving, generalization, and mathematical modeling. The instrument's reliability is 0.759, categorized as reliable. In this study, the majority of the developed items fell into the medium difficulty category, totaling 16 items. Only one item was in the easy category, and none fell into the difficult category